Implementation of Reliable Fault Tolerant Data Storage System over Cloud using Raid – 60 - Singh, Parminder; Bisht, Sheetal (International Journal of Computer Sciences and Engineering, 2025)
Cloud computing has emerged as an outstanding service delivery model. Almost all the organizations are switching to cloud in order to avoid the infrastructural cost and utilize the other benefits of the cloud services. As we know with benefits there come the issues, with tremendous increase in growth of technology, huge amount of data is being stored in cloud. Storage of data in cloud requires a high cost of adaptability in order to provide an efficient, reliable and fault tolerance data storage system. Currently fault tolerance is handled by service provider or customer, which is an ineffective way of handling the fault tolerance and lead to in efficient solution. Rather than handling the problem over the service provider or customer this paper deals with an effective and innovative way of handling the fault tolerance in cloud. In this paper we propose a high level approach by deploying the RAID-60 technology to service the fault tolerance problem in cloud.